1994
DOI: 10.5032/jae.1994.04042
|View full text |Cite
|
Sign up to set email alerts
|

Participation Of FFA Members In Leadership Development Activities: A Tri-State Study

Abstract: The development of "competent and assertive agricultural leadership" is a purpose of the National FFA Organization (1993, p. i). Research has provided limited, and often perceptual and correlational, evidence that participation in the FFA develops leadership skills. Brannon, Holley, and Key (1989) found Oklahoma community leaders who had participated in vocational agriculture and FFA in high school felt such participation contributed to their leadership development. They also felt vocational agriculture/FFA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
(4 reference statements)
2
16
0
Order By: Relevance
“…Length of FFA membership did not indicate a relationship to the self-perceived leadership skills of the WLC participants. However, results concerning level of FFA involvement supported research of several authors (Townsend & Carter, 1983;Ricketts & Newcomb, 1984;Dormody & Seevers, 1994;Wingenbach & Kahler, 1997) who found that leadership traits of youth are enhanced by participation in FFA activities. This study supports the findings of Ricketts and Newcomb (1984), who found a correlation between the leadership abilities of FFA members and the level of activity by an individual within the chapter.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Length of FFA membership did not indicate a relationship to the self-perceived leadership skills of the WLC participants. However, results concerning level of FFA involvement supported research of several authors (Townsend & Carter, 1983;Ricketts & Newcomb, 1984;Dormody & Seevers, 1994;Wingenbach & Kahler, 1997) who found that leadership traits of youth are enhanced by participation in FFA activities. This study supports the findings of Ricketts and Newcomb (1984), who found a correlation between the leadership abilities of FFA members and the level of activity by an individual within the chapter.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…The researchers further indicated that high expectations held by FFA members, combined with a high level of performance expected by others, yielded a positive relationship with the leadership life skills development scale. Female FFA members also had higher leadership life skill development indicators than the male members (Dormody & Seevers, 1994). Wingenbach and Kahler (1997) replicated the Dormody and Seevers (1994) (Townsend & Carter, 1983;Dodson, 1995), collegiate women (Thorp et al, 1998), and 4-H Club members (Boyd, 1991).…”
Section: Ffa Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…In a study of past FFA participation in the role of community leadership development, Brannon, Holley and Key (1989) found that former FFA members had an impact on the development and success of community leaders. Dormody and Seevers (1994) found that three variables-achievement expectancy, participation in FFA leadership activities and gender-were significant in predicting the leadership life skill development of members. A follow-up study by Wingenbach and Kahler (1997) supported these findings.…”
Section: Organizational Elements Of Ctsosmentioning
confidence: 95%